2013
DOI: 10.18172/cig.1205
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias estacionales en la generación de escorrentía en una pequeña cuenca de campos abandonados en el Pirineo Central

Abstract: RESUMEN. Este trabajo muestra que las relaciones entre precipitación y escorrentía a escala de crecida en una pequeña cuenca de campos abandonados no

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…However, a variability throughout the seasons can be observed, especially in late autumn and early spring, as these are transition periods. Additionally, Lana-Renault [10] observed that the wetting-up period was steeper than the drying-down period, which was more progressive in a catchment located in the Pyrenees. Autumn was the season after the driest period, and it was when the evapotranspiration reached the maximum values.…”
Section: Small Mediterranean-climate Catchments: Lithology Influencesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a variability throughout the seasons can be observed, especially in late autumn and early spring, as these are transition periods. Additionally, Lana-Renault [10] observed that the wetting-up period was steeper than the drying-down period, which was more progressive in a catchment located in the Pyrenees. Autumn was the season after the driest period, and it was when the evapotranspiration reached the maximum values.…”
Section: Small Mediterranean-climate Catchments: Lithology Influencesmentioning
confidence: 99%
“…Different seasonal rainfall-runoff relationships in relation to the influence of rainfall and evapotranspiration [56] are related to the alternation of rainfall and reference evapotranspiration throughout the year reproducing wet (winter), dry (summer) and transition periods (last autumn and early spring) [57]. Accordingly, winter is the season with the highest R c , from 17% to 56%, due to rainfall being accumulated during autumn-and maintained in winter-and low evapotranspiration demand [10,15,56]. The same pattern was also observed during the five hydrological years assessed in Es Fangar Creek.…”
Section: Small Mediterranean-climate Catchments: Lithology Influencesmentioning
confidence: 99%
See 3 more Smart Citations